Human mast cells promote colon cancer growth via bidirectional crosstalk: studies in 2D and 3D coculture models. (2nd November 2018) - Yu, Yingxin; Blokhuis, Bart; Derks, Yvonne; Kumari, Sangeeta; Garssen, Johan; Redegeld, Frank
ABSTRACT: Chronic inflammation drives the development of colorectal cancer (CRC), where tumor-infiltrating immune cells interact with cancer cells in a dynamic crosstalk. Mast cells (MC), one of earliest recruited immune cells, accumulate in CRC tissues and their density is correlated with cancer progression. However, the exact contribution of MC in CRC and their interaction with colon cancer cells is poorly understood. Here, we investigated the impact of primary human MC and their mediators on colon cancer growth using 2D and 3D coculture models. Primary human MC were generated from peripheral CD34 + stem cells. Transwell chambers were used to analyze MC chemotaxis to colon cancer. Colon cancer cells HT29 and Caco2 differentially recruited MC by releasing CCL15 or SCF, respectively. Using BrdU proliferation assays, we demonstrated that MC can directly support colon cancer proliferation and this effect was mediated by their cellular crosstalk. 3D coculture models with cancer spheroids further confirmed the pro-tumor effect of MC on colon cancer growth, where direct cell-cell contact is dispensable and increased production of multiple soluble mediators was detected. Moreover, TLR2 stimulation of MC promoted stronger growth of colon cancer spheroids. By examining the transcriptome profile of colon cancer-cocultured MC versus control MC, we identified several MC marker genes, which were deregulated in expression. Our study provides an advanced in vitro model to investigate the role of human MC in cancer. Our data support the detrimental role of MC in CRC development and provide a molecular insight into the cellular crosstalk between MC and colon cancer cells.